Proximal point algorithms involving fixed points of nonexpansive mappings in CAT(0) spaces - Cholamjiak, Prasit; Abdou, Afrah AN; Cho, Yeol Je (Fixed point theory and applications (Hindawi Publishing Corporation), 2015)
In this paper, we introduce a new modified proximal point algorithm involving fixed point iterates of nonexpansive mappings in CAT ( 0 ) spaces and prove that the sequence generated by our iterative process converges to a minimizer of a convex function and a fixed point of mappings.